A educação dos sentidos no método de ensino intuitivo e o caso das escolas públicas isoladas de São Paulo (1889-1910) - Rozante, Ellen Lucas (2013)
This research aimed to investigate how the senses were educated in the school in order that people were promptly inserted into the social world, since the school has contributed to the ordering and organization of society through disciplinary education of the body. More specifically, this work aimed to study the education in the intuitive method, highlighting the importance of senses and their training by this method; it also tried to detect pedagogical practices, especially in isolated schools that kept the education of body, in a time when it was necessary teaching the control of emotional reactions at the same time that the instruction was needed for a peaceful political participation, besides checking, through the lessons of things , how the notion of experience structured the education of the senses. The thematic delimitation of this research is the education of the senses through the intuitive method, that was discussed and inserted into the educational context at the end of the nineteenth century, as a model of renovation and modernization of education in the early years of the Republic. The spatial area was the province of São Paulo, because it has extreme responsibility in spreading the intuitive method in primary education, prescribing it as official teaching method, besides being presented as the birthplace of the modern school. The time delimitation of this research was the closing years of the nineteenth century, highlighting the nascent republic in 1889 until around 1910, when the new model has been consolidated, even to the point where its crisis started. The guiding questions were: If the intuitive method has been the symbol of renewal in the Brazilian nascent republic, and a way to conform, civilize and modernize the republican citizen, how was characterized the education of the senses that it preached so much? If this method was based on intuition by the senses, i.e. by direct contact with things, with its perception by intuition, manipulation and experimentation, aiming to gradually introduce arguments, how would be this education of the senses in the intuitive method? How was the teaching of seeing, hearing, smelling, touching and tasting in the prescriptions and pedagogical practices? The hypothesis that guided this study is: there was a training of the senses through the intuitive method, which should form and conform a new man. We can understand that such training was not random: seeing, hearing, smellin, feeling (touching) and tasting were not seen as a casual education, but they were rather channeled and hierarchically ranked, in order to configurate the experiences and sensibilities required for the Nation. The documental corpus of this research was formed by three sets of documents. The criteria division of this set were: first, bibliographies produced in that period, as the manual First Lessons of Things by Norman Alison Calkins, Dictionnaire de Pédagogie by Ferdinand Buisson, Reform of Primary Education by Rui Barbosa and some textbooks and reading books. The second set of sources for this work was the pedagogical press of that period, more precisely the Eschola Publica Magazine (1893-1896) and the Teaching Magazine of Benevolent Association of Public Professorship of São Paulo (1902-1919). Finally, the last set of sources were documents relating to Public Instruction, found in the collections of the State Archives of São Paulo (AESP), such as reports of public school teachers, inspectors and schoolmasters, beside several letters and inventorial materials. The investigation concluded that, considering the speeches on streamlining and scientificity in that period, the intuitive method honored modern aspirations, i.e. educating and civilizing. The senses were methodically arranged, converging into an objective education. Among prescriptions idealized, the isolated practices in schools were according to the possibilities for those who were not civilized in kindness of gestures or politeness habits. At least they fulfilled the maintenance of social order